Parental Socioeconomic Status and Early Childhood Self-Confidence: A Correlational Study - Mona Yulia Zulfa; Suci Nadiati Rahma (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
Self-confidence is one of the essential psychological attributes that supports children’s social and academic development in early childhood education. Family background, particularly parents’ socioeconomic status, is often considered a determining factor in shaping children’s self-perception and confidence. This study aims to examine the relationship between parents’ socioeconomic status and the self-confidence of early childhood students. A quantitative research method with a descriptive correlational approach was employed. The participants consisted of ten early childhood students from one educational institution. Data were collected through validated questionnaires and teacher reports, then analyzed using correlation techniques with SPSS 26. The findings revealed a significant relationship between parents’ socioeconomic status and children’s self-confidence (p < 0.05). These results highlight that socioeconomic conditions play a crucial role in fostering children’s psychological growth, particularly their confidence in learning and social interaction. The study provides practical implications for educators and policymakers to design interventions that strengthen self-confidence among children from diverse socioeconomic backgrounds, while also offering a foundation for future research in early childhood education.